Sanitary conditions of private and public swimming-pools in Araraquara, State of S. Paulo, Brazil - Mendonça, Clara Pechmann; Ruff, Suzana Debora (Revista de Saúde Pública, 1978)
Taking into account that swimming is excelent exercise for health in general, and has been prefered as a sport by people of all ages and both sexes, and that the liquid mass contained in tanks can transmit diseases, a study was undertaken in order to verify the hygienic conditions of some of the public and private swimming pools in the City of Araraquara, State of S. Paulo, Brazil. Thirty-six samples of water from public swimming pools and 22 from private ones were taken. It was verified that, although receiving a specific treatment, they did not maintain sufficient chlorine levels to restrain the proliferation of bacteria, some of which dangerous to the health of bathers. Likewise, chloride levels were seen to be high, which indicate that the water was contaminated by urine or even by sweat, leading to the conclusion that bathers must receive adequate instruction.